Kedudukan dan Akibat Hukum Surat Kuasa Membebankan Hak Tanggungan Menurut Undang-Undang No. 4 Tahun 1996 Tentang Hak Tanggungan - Ajas Renaldi (Faculty of Sharia and Law State Islamic University Syarif Hidayatullah Jakarta, 2022)
This article aims to find out the position and consequences of the power of attorney under Law No. 4 of 1996 on Dependent Rights. The application for credit to a bank must be backed up by juridical and economic elements, so that between the rights and responsibilities of both parties become clear and certain. The writing of this article uses normative juridical research methods. The results of this article show that the Position of Power of Attorney Charging Dependent Rights According to Law No. 4 of 1996 on Dependent Rights is an authentic deed made by a notary or Land Deed Making Officer, If the dependent rights giver cannot present themselves before the PPAT to make the Deed of Granting Dependent Rights (APHT). As a result of the Power of Attorney's Rights Charging Dependent Rights that is the power to charge dependent rights can not be withdrawn or cannot end for any reason except because the power has been exercised or because it has expired.